The influence of behavioral factors in investment decisions: study of millennial investors in Kuala Lumpur - Loh, Tong Cheng (2016)
Traditionally, investing is viewed as a rational activity which is carried out based on one’s financial objectives. However, newer theories in investment behaviour view investing as a behavioural science, acknowledging that investors are human beings influenced by behavioural investment factors. This study surveyed 200 millennial investors from Kuala Lumpur, Malaysia, in order to investigate the behavioural factors that affect their investment decision. Millennial investors refer to investors between the ages of 21 to 36 years old. Specifically, this study examines the factors which influence millennial investors’ investment decision based on heuristic theory, prospect theory, market factors, and herding effect. Data collection is done through a questionnaire which is shared online. The findings reveal that both traditional finance theory and behavioural finance theory’s factors influence the respondents’ investment decision. Nevertheless, the behavioural finance theory’s factors of heuristics theory and herding effect have greater impact compared to traditional finance theory’s factors. In addition, it is revealed that Malaysian investors in Kuala Lumpur perceive themselves to be more rational than they actually are.